2013
DOI: 10.1245/s10434-013-3287-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ileostomy-Related Complications on the Multidisciplinary Treatment of Rectal Cancer

Abstract: Background Radical resection is the primary treatment for rectal cancer. When anastomosis is possible, a temporary ileostomy is used to decrease morbidity from a poorly healed anastomosis. However, ileostomies are associated with complications, dehydration, and need for a second operation. Our purpose was to evaluate the impact of ileostomy related complications on the treatment of rectal cancer. Methods A retrospective cohort study of patients who underwent sphincter preserving surgery between January 2005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 26 publications
5
71
1
3
Order By: Relevance
“…Such concerns appear valid, given the increased wound infection rates associated with early closure. However, recent studies have also demonstrated defunctioning loop ileostomies and ileostomy-related complications to be independent risk factors in both the delayed administration and omission of adjuvant chemotherapy [34,35]. Consequently, EC could potentially result in the improved delivery of adjuvant chemotherapy; however, further studies evaluating early ileostomy closure in the setting of adjuvant chemotherapy administration are still required.…”
Section: Discussionmentioning
confidence: 99%
“…Such concerns appear valid, given the increased wound infection rates associated with early closure. However, recent studies have also demonstrated defunctioning loop ileostomies and ileostomy-related complications to be independent risk factors in both the delayed administration and omission of adjuvant chemotherapy [34,35]. Consequently, EC could potentially result in the improved delivery of adjuvant chemotherapy; however, further studies evaluating early ileostomy closure in the setting of adjuvant chemotherapy administration are still required.…”
Section: Discussionmentioning
confidence: 99%
“…However, diverting loop‐ileostomy potentially increases the risks for stoma‐related complications including small bowel obstruction (SBO), stoma prolapse, stoma retraction, parastomal hernia, parastomal dermatitis, and mucocutaneous dehiscence. Risks for stoma‐related complications are reportedly 5‐46% 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diverting stoma also increases patient discomfort, overall cost, and the duration of hospitalization since the patient will need a second operation for closure of the stoma [17,18]. Phatak et al [19] reported that diverting ileostomies are associated with a significant risk for ileostomy-related morbidity including dehydration and perioperative complications of stoma closure. Although this morbidity may be balanced by the benefit of decreasing anastomosis leak, these disadvantages should be considered.…”
mentioning
confidence: 99%